Impact of two-step urine culture ordering in the emergency department: a time series analysis. Issue 2 (3rd May 2017) - Stagg, Amanda; Lutz, Haydon; Kirpalaney, Sakshi; Matelski, John Justin; Kaufman, Adam; Leis, Jerome; McCready, Janine; Powis, Jeff
Abstract : Background: Despite evidence against the use of antimicrobials for asymptomatic bacteriuria (ASB), they are frequently prescribed leading to unnecessary adverse events. Prior studies have shown that reducing unnecessary urine cultures (UCs) results in decreased antimicrobial utilisation for ASB. Emergency departments (EDs) submit the largest volume of UCs, yet efforts to limit overordering in this patient setting have had limited success. Methods: A new two-step model of care for urine collection, using a novel UC collection container, was implemented in the ED of a large community hospital. The collection system contains a preservative allowing UCs to be held at room temperature for up to 48 hours before processing. UCs were collected by front-line staff, but only processed in the microbiology lab if requested by ED physicians after clinical assessment. Results: Following implementation there was a decrease in the percentage of weekly ED visits associated with a processed UC (5.97% vs 4.68%, p<0.001), a decrease in the percentage of monthly ED visits requiring a callback for positive urine culture (1.84% to 1.12%, p<0.001) and a decrease in antimicrobial prescriptions for urinary indication among admitted patients (20.6% to 10.9%, p<0.01). There was a false omission rate of 1.35% (95% CI 0.7% to 2.2%), yet no identified cases of untreated urinary tract infection (UTI), or significant change in repeat ED visits or ED length of stay. Conclusions: Changing to two-step urine culture ordering in the ED resulted in a decrease in UCs processed, callbacks for positive results and antimicrobial use without evidence of untreated UTIs. This model of care has strong potential to improve the use of hospital resources while minimising detection and inappropriate treatment of ASB.